2022
DOI: 10.1007/s00415-022-11402-6
|View full text |Cite
|
Sign up to set email alerts
|

The idiopathic intracranial hypertension prospective cohort study: evaluation of prognostic factors and outcomes

Abstract: Background There are limited longitudinal data evaluating outcomes in idiopathic intracranial hypertension (IIH). We aimed to evaluate the long-term outcomes in a real-world cohort of patients with IIH and sought to establish the prognostic factors. Methods A longitudinal prospective cohort study was conducted over 9 years (2012–2021). Data included demographics and disease status. All consenting patients with IIH were recruited. Visual outcomes included v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 56 publications
(78 reference statements)
1
27
0
Order By: Relevance
“…The observed ICP of the HFD-fed rats was approximately 65% higher than that of the control animals, which aligns with the earlier reports on such rat models [35, 70]. However, this ICP elevation is lower than the (minimum) doubling of the mean lumbar opening pressure observed in IIH patients compared to healthy control subjects [72]. Therefore, although these overweight rats appear to recapitulate the cardinal phenotype of IIH symptomatology, elevated ICP, this model cannot mimic the magnitude of ICP change seen in IIH.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed ICP of the HFD-fed rats was approximately 65% higher than that of the control animals, which aligns with the earlier reports on such rat models [35, 70]. However, this ICP elevation is lower than the (minimum) doubling of the mean lumbar opening pressure observed in IIH patients compared to healthy control subjects [72]. Therefore, although these overweight rats appear to recapitulate the cardinal phenotype of IIH symptomatology, elevated ICP, this model cannot mimic the magnitude of ICP change seen in IIH.…”
Section: Discussionsupporting
confidence: 89%
“…However, when mimicking the elevated testosterone environment, as observed in patients with IIH, we observed CSF hypersecretion in the experimental rats. Synergic effects of obesity and hyperandrogenism may thus, if sustained for prolonged time and potentially associated with other IIH-promoting factors [28, 59, 72], provide a mechanistic coupling to the elevated ICP observed in the IIH patients. Future in vivo animal studies combining obesity and androgen excess may reveal further pieces of the IIH etiology, and androgen blockade, in the context of obesity, may elucidate avenues for therapeutic targeting in IIH.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 These data show marked variability in headache outcomes, which reflects what has been found in the IIH population as a whole. 37 Headache frequency was high at baseline (Figure 3) in groups 2, 3, and 4 with either mild improvement or stability over time (Table 2). This plateau was also seen for migraine-like headache frequency, headache severity, and HIT-6 score and highlights the need for new treatment options for the management of persistent post-IIH headache, which has been called for by patients and physicians.…”
Section: Discussionmentioning
confidence: 97%
“…In group 1, we also noted a trend toward declining PMD and worsening papilledema measured by OCT imaging (Figure 2). We have previously shown that acute IIH has more severe papilledema than chronic IIH, 37 so there is the possibility that newly diagnosed IIH in pregnancy would have more severe papilledema than those with more chronic IIH who become pregnant. Those patients with IIH diagnosed in pregnancy (group 1) were interesting in that papilledema worsened during the 12 months following diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation